Formulation, release characteristics, and bioavailability study of gastroretentive floating matrix tablet and floating raft system of Mebeverine HCl - El Nabarawi MA; Teaima MH; Abd El-Monem RA; El Nabarawy NA; Gaber DA (Dove Medical Press, 2017)
Mohamed A El Nabarawi,1 Mahmoud H Teaima,1 Rehab A Abd El-Monem,2 Nagla A El Nabarawy,3 Dalia A Gaber4 1Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Cairo University, Cairo, Egypt; 2Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Misr University for Science and Technology, 6th of October, Egypt; 3National Egyptian Center of Environment and Toxicological Research (NECTER), Faculty of Medicine, Cairo University, Cairo, Egypt; 4Department of Quality Control, Holding Company for Biological Products and Vaccines, Cairo, Egypt Abstract: To prolong the residence time of dosage forms within the gastrointestinal tract until all drug is released at the desired rate is one of the real challenges for oral controlled-release drug delivery systems. This study was designed to develop a controlled-release floating matrix tablet and floating raft system of Mebeverine HCl (MbH) and evaluate different excipients for their floating behavior and in vitro controlled-release profiles. Oral pharmacokinetics of the optimum matrix tablet, raft system formula, and marketed Duspatalin® 200 mg retard as reference were studied in beagle dogs. The optimized tablet formula (FT-10) and raft system formula (FRS-11) were found to float within 34±5 sec and 15±7 sec, respectively, and both remain buoyant over a period of 12 h in simulated gastric fluid. FT-10 (Compritol/HPMC K,100M 1:1) showed the slowest drug release among all prepared tablet formulations, releasing about 80.2% of MbH over 8 h. In contrast, FRS-11 (Sodium alginate 3%/HPMC K,100M 1%/Precirol 2%) had the greatest retardation, providing sustained release of 82.1% within 8 h. Compared with the marketed MbH product, the Cmax of FT-10 was almost the same, while FRS-11 maximum concentration was higher. The tmax was 3.33, 2.167, and 3.0 h for marketed MbH product, FT-10, and FRS-11, respectively. In addition, the oral bioavailability experiment showed that the relative bioavailability of the MbH was 104.76 and 116.01% after oral administration of FT-10 and FRS-11, respectively, compared to marketed product. These results demonstrated that both controlled-released floating matrix tablet and raft system would be promising gastroretentive delivery systems for prolonging drug action. Keywords: GRDDS, Precirol®, Compritol®, HPMC, Na alginate